Civil Servant Mutation Determination System Based on Performance and Competence Using the Method Organization, Rangement and Synthesis of Relational Data (Oreste) - Victor Ilyas Sugara Sugara (Program Studi Ilmu Komputer, Universitas Pakuan, 2026)
This study discusses the development of a Decision Support System (DSS) to determine the mutation of Civil Servants (PNS) at the Center for Standardization of Food Crop Instruments (PSITP) Bogor using the methodOrganization Rangement Et Synthese De Donnes Relationnelles (ORESTE).The previous transfer process was still done manually using Excel, making it prone to calculation errors, lacking objectivity, and taking a long time. This research aims to develop a web-based system capable of assessing employee performance and competency in a more accurate, transparent, and structured manner. The data used includes 40 employees and their performance and competency scores, obtained through interviews and field research. MethodsORESTESused because it is able to process rankings withBesson Rankwhen there are the same criteria values, then calculateDistance Scoreto produce a preference value (Vi) which determines the final ranking of employees who are worthy of being transferred. The system development uses the methodWaterfall which includes needs analysis, system design, implementation withPHP And MySQL, testing, and maintenance. The resulting system provides login features for admins, employees, and center heads; performance and competency data management; and automatic calculations usingORESTES; and the display of employee ranking results. Structural, functional, and validation tests showed that the system ran as required and was able to provide accurate calculation results. The research results concluded that the methodORESTESIt is effective in civil servant transfer decision-making because it produces objective rankings based on a combination of performance and competency. The developed decision support system also speeds up the transfer process, minimizes human error, and increases transparency and accuracy in determining which employees are eligible for transfer.